Macroeconomic changes and trends in dental care utilization in Estonia and Lithuania in 2004-2012: a repeated cross-sectional study - Mall Leinsalu; Rainer Reile; Kaire Vals; Janina Petkeviciene; Mare Tekkel; Andrew Stickley (BMC, 2018)
Abstract Background The aim of this study was to assess trends and inequalities in dental care utilization in Estonia and Lithuania in relation to large-scale macroeconomic changes in 2004-2012. Methods Data on 22,784 individuals in the 20-64 age group were retrieved from nationally representative cross-sectional surveys in 2004, 2006, 2008, 2010 and 2012. Age- and sex-standardized prevalence estimates of past 12-month dental visits were calculated for each study year, stratified by gender, age group, ethnicity, educational level and economic activity. Multivariable logistic regression analysis was used to assess the independent effect of study year and socioeconomic status on dental visits. Results The age- and sex-standardized prevalence of dental visits in the past 12 months was 46-52% in Estonia and 61-67% in Lithuania. In 2004-2008, the prevalence of dental visits increased by 5.9 percentage points in both countries and fell in 2008-2010 by 3.8 percentage points in Estonia and 4.6 percentage points in Lithuania. In both countries the prevalence of dental care utilization had increased slightly by 2012, although the increase was statistically insignificant. Results from a logistic regression analysis showed that these differences between study years were not explained by differences in socioeconomic status or oral health conditions. Women, the main ethnic group (only in Estonia), and higher educated and employed persons had significantly higher odds of dental visits in both countries, but the odds were lower for 50-64 year olds in Lithuania. Conclusions In European Union countries with lower national wealth, the use of dental services is sensitive to macroeconomic changes regardless of the extent of public coverage, at the same time, higher public coverage may not relate to lower inequalities in dental care use.